Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5194/bg-16-1685-2019
|View full text |Cite
|
Sign up to set email alerts
|

Grazing-related nitrous oxide emissions: from patch scale to field scale

Abstract: Abstract. Grazed pastures are strong sources of the greenhouse gas nitrous oxide (N2O). The quantification of N2O emissions is challenging due to the strong spatial and temporal variabilities of the emission sources and so N2O emission estimates are very uncertain. This study presents N2O emission measurements from two grazing systems in western Switzerland over the grazing season of 2016. The 12 dairy cows of each herd were kept in an intensive rotational grazing management. The diet for the two herds of cows… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
(69 reference statements)
3
14
1
Order By: Relevance
“…The N 2 O EFs observed for urine and dung in the current study might be related to the soil, climate, and management practices. Previous studies conducted in similar climates [25,[27][28][29][30] reported low EFs for urine and dung in line with our findings. De Klein et al [53] and Marsden et al [26] reported low (0.03-0.3%) N 2 O-N EF for animal excreta deposited on free-draining soils.…”
Section: N 2 O Emissions and Emission Factorssupporting
confidence: 93%
See 2 more Smart Citations
“…The N 2 O EFs observed for urine and dung in the current study might be related to the soil, climate, and management practices. Previous studies conducted in similar climates [25,[27][28][29][30] reported low EFs for urine and dung in line with our findings. De Klein et al [53] and Marsden et al [26] reported low (0.03-0.3%) N 2 O-N EF for animal excreta deposited on free-draining soils.…”
Section: N 2 O Emissions and Emission Factorssupporting
confidence: 93%
“…In accordance, recent studies [25][26][27][28][29][30] have reported low N 2 O-N emission factors (EFs) for urine and dung patches in improved grazing management systems, compelling the Intergovernmental Panel on Climate Change (IPCC) to revise the IPCC [31] default emission factor from 2 to 0.77% for wet temperate climates [32]. In this study, we assessed the applicability of the revised default N 2 O EF [32] to an organic dairy farm located on a sandy loam soil in northern Germany.…”
Section: Of 26supporting
confidence: 91%
See 1 more Smart Citation
“…While techniques exist to directly measure total N 2 O emissions at a field scale, e.g. the eddy covariance method, data acquired in this manner can neither be used to quantify source-specific EFs nor identify mechanistic pathways linking grazing management strategies and resultant emissions ( Voglmeier et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the key component required for monitoring GHGs, nutrient cycle, soil health, and grass regrowth is the patch excretions and preferences of animals within a paddock, which ultimately determines grass and nutrient heterogeneity. Failure to integrate plant and animal processes at appropriate temporal and spatial scales can result in an incorrect representation of field scale for grazing land management (Voglmeier et al, 2019). Therefore, causal relationships between animal activity, grazing intensity and frequency are challenging to establish but remain fundamental to building the grazing model and understanding these causal links.…”
Section: Urine Patches and Selecting Pasture Due To Animal Movementmentioning
confidence: 99%